Children's Rights, not Deceptive Patterns by Design: a Requirements Perspective - Valença, George; Silva, João Victor; Rocha, Beatriz; Cortiz, Diogo (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
In the digital age, children are frequent users of software platforms, yet they often lack awareness of various cyber risks such as theft, stalking, and harassment. These and other online issues are favoured by deceptive design patterns introduced by IT companies in their solutions, such as game apps and social media. These patterns may deceive or manipulate users into taking unintended actions, such as making purchases, signing up for services or leaving loose privacy definitions. This paper aims to understand the relationship between deceptive patterns and needed measures for a safe online experience for children. We accomplish this goal by analysing how deceptive design patterns affect a list of eighteen legal software requirements for children’s protection and well-being online, based on guidelines from UNICEF (The United Nations Children’s Fund). Our contribution is twofold: (i) describing how IT companies neglect such legal requirements and (ii) discussing essential safeguards by adapting or incorporating new features, presented here as prototypes. By investigating this relationship, we seek to provide insights into how to design software solutions that protect children and ensure their rights online